Robert Moran, 1890 - Wilse, Anders B.
Robert Moran was born in New York City and came to Seattle in 1875. After working on ships for a number of years, he and his brothers opened a marine repair shop at Yesler's Wharf in 1882. Over the years, Moran Brothers Company gained an excellent reputation for repairing and building ships. Among other vessels, the company built Yukon River steamboats for the gold rush and and the battleship "Nebraska" for the U.S. Navy. This photo shows Robert Moran in his office at the Moran Brothers Company. Moran was Mayor of Seattle at the time of the Great Fire of 1889. After selling the company in 1906, Moran retired to Rosario, his estate on Orcas Island. He died in 1943 at age 86. 1 photographic print: b&w; 14 x 19 cm.